Modeling Social Sensory Processing During Social Computerized Cognitive Training for Psychosis Spectrum: The Resting-State Approach - Kambeitz-Ilankovic, Lana; Wenzel, Julian; Haas, Shalaila S.; Ruef, Anne; Antonucci, Linda A.; Sanfelici, Rachele; Paolini, Marco; Koutsouleris, Nikolaos; Biagianti, Bruno (Frontiers in Psychiatry, 2020)
Background: Greater impairments in early sensory processing predict response to auditory Computerized Cognitive Training (CCT) in patients with Recent Onset Psychosis (ROP). Little is known about neuroimaging predictors of response to social CCT, an experimental treatment that was shown to induce cognitive improvements in patients with psychosis. Here, we investigated whether ROP patients show inter-individual differences in sensory processing change and whether different patterns of SPC are 1) related to differential responses to treatment, as indexed by gains in social cognitive tests and 2) associated with unique resting state Functional Connectivity (rsFC). Methods: 26 ROP patients completed 10 hours of CCT over 4-6 weeks. Subject-specific improvement in one CCT exercise targeting early sensory processing – a speeded facial Emotion Matching Task (EMT) – was studied as potential proxy for target engagement. Based on the median split of SPC from the EMT, two patient groups were created. Resting state activity was collected at baseline and bold time series were extracted from two major Default Mode Network (DMN) hubs: left medial prefrontal cortex (mPFC) and left posterior cingulate cortex (PCC). Seed rsFC analysis was performed using standardized Pearson correlation matrices, generated between the average time course for each seed and each voxel in the brain. Results: Based on SPC, we distinguished improvers – i.e., participants who showed impaired performance at baseline and reached the EMT psychophysical threshold during CCT – from maintainers – i.e., those who showed intact EMT performance at baseline and sustained the EMT psychophysical threshold throughout CCT. Compared to maintainers, improvers showed an increase of rsFC at rest between PCC and left superior and medial frontal regions and the cerebellum. Compared to improvers, maintainers showed increased rsFC at baseline between PCC and superior temporal and insular regions bilaterally. Conclusions: In ROP patients with an increase of connectivity at rest in the default mode network, social CCT is still able to induce sensory processing changes that however do not translate into social cognitive gains. Future studies should investigate if impairments in short-term synaptic plasticity are responsible for this lack of response and can be remediated by pharmacological augmentation during CCT.